2004
DOI: 10.1007/bf02254359
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective role of heat shock protein 70 in the rostral ventrolateral medulla during acute mevinphos intoxication in the rat

Abstract: Heat shock protein (HSP) is a family of highly conserved proteins that respond to stress and participate actively in cytoprotection. Within the HSP family, HSP70 is the major inducible member that confers protection against cell death. This study investigated whether HSP70 plays a neuroprotective role at the rostral ventrolateral medulla (RVLM), the origin of sympathetic neurogenic vasomotor tone in the medulla oblongata where the organophosphate insecticide mevinphos (Mev) acts to elicit cardiovascular toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The neuroprotective role of HSP70 in the rat brain has been studied previously by using an anti-HSP70 Ab (antibody) [20,21]. A neutralizing polyclonal rabbit anti-(mouse HSP70) Ab (0.2 mg/kg of body weight; SPA-812E; Assay Designs) dissolved in non-pyrogenic sterile saline was injected intravenously 24 h prior to simulated HAE.…”
Section: Inhibition Of Hsp70 Activitymentioning
confidence: 99%
“…The neuroprotective role of HSP70 in the rat brain has been studied previously by using an anti-HSP70 Ab (antibody) [20,21]. A neutralizing polyclonal rabbit anti-(mouse HSP70) Ab (0.2 mg/kg of body weight; SPA-812E; Assay Designs) dissolved in non-pyrogenic sterile saline was injected intravenously 24 h prior to simulated HAE.…”
Section: Inhibition Of Hsp70 Activitymentioning
confidence: 99%
“…In addition to transcriptional regulation, c-Jun also mediates posttranscriptional modification on HIF-1α by protecting it from proteasomal degradation [66]. Interestingly, all these proteins have been found to play a pro-life role in RVLM in our experimental model of brain stem death [16,67-71]. Fischer et al, [72] reported that marked increases in JNK and p38MAPK activity, coincident with an increase in phosphorylation of c-Jun and ATF-2, can be detected as early as 15–30 min after rapid changes in hemodynamic load in Wistar rats.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory, anti-oxidative, and anti-apoptotic qualities make taurine neuroprotective. Taurine inhibits pro-inflammatory cytokines and chemokines in activated microglia and astrocytes, reducing neuroinflammation (Chang et al, 2015).…”
Section: Taurine Neuroprotectionmentioning
confidence: 99%
“…Taurine protects neurones in animal models of Alzheimer's, Parkinson's, Huntington's, and multiple sclerosis (Wu et al, 2016). Taurine reduces amyloid-beta deposition and neuroinflammatory reactions in animal models of Alzheimer's disease, improving cognition (Chang et al, 2015). Taurine improves motor deficits and dopaminergic neurone loss in animal models of Parkinson's disease (Wu et al, 2016).…”
Section: Patient Treatment Implicationsmentioning
confidence: 99%